Access to Energy Consumption and Economic Growth: Evidence from South Asian Perspective - Zahid, Hesan; Jillani, Hammna; Sabolovič, Mojmír (International Journal of Energy Economics and Policy, 2026)
This study investigates the relationship between energy access and economic growth in selected South Asian economies, i.e., Pakistan, India, Bangladesh, and Sri Lanka, using panel data from 2000 to 2022. Employing a panel ordinary least squares (OLS) framework with robust standard errors and country-specific effects, the analysis distinguishes between different dimensions of energy access, including electricity access, clean cooking fuel access, and per capita energy consumption. The results reveal that while electricity access alone does not exert a statistically significant immediate impact on GDP growth, per capita energy consumption exhibits a strong positive association with economic performance. In contrast, access to clean fuels for cooking shows a weak negative relationship with short-term economic growth, suggesting transitional and structural adjustment effects. Inflation is found to exert a dampening effect on growth, highlighting the importance of macroeconomic stability. Country-specific results reveal substantial heterogeneity, with Bangladesh and India demonstrating stronger growth effects relative to Sri Lanka. The findings underscore that expanding energy access must be accompanied by reliable supply, productive energy use, and supportive macroeconomic conditions to effectively contribute to economic growth. The study provides policy-relevant insights aligned with Sustainable Development Goals 7 and 8.